EP activity evaluation of some 2-phenyl-3-phenylimino-5-arylimino-1,2,4-thiadiazolidines - Singh T.; Bhattacharya A.; Verma V.K. (My University, 2025)
A four-ball test was conducted to evaluate the EP activity of 2-phenyl-3-phenylimino-5-arylimino-1,2,4-thiadiazolidines (0.5% w/v) in paraffin base oil using a 12.7-mm diameter steel ball specimen. 2-phenyl-3-phenylimino-5-p-chlorophenylimino-1,2,4-thiadiazolidine exhibited good activity in reducing wear scar diameter and friction coefficient values at higher loads and increasing the values of flash temperature parameter (FTP), mean Hertz load (MHL) and pressure wear index (PWI) as compared with commercially available sulphur-phosphorous reference additives. The wear surface tribochemistry and topography were investigated using scanning Auger electron spectroscopy and scanning electron microscopy techniques. © 1991.